2013
DOI: 10.1371/journal.pone.0076402
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressive Function of mir-205 in Breast Cancer Is Linked to HMGB3 Regulation

Abstract: Identifying targets of dysregulated microRNAs (miRNAs) will enhance our understanding of how altered miRNA expression contributes to the malignant phenotype of breast cancer. The expression of miR-205 was reduced in four breast cancer cell lines compared to the normal-like epithelial cell line MCF10A and in tumor and metastatic tissues compared to adjacent benign breast tissue. Two predicted binding sites for miR-205 were identified in the 3’ untranslated region of the high mobility group box 3 gene, HMGB3. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 30 publications
(38 reference statements)
6
73
0
Order By: Relevance
“…Recent study of Nemeth et al [39] showed that HMGB3 played a key role in regulating the balance between proliferation and differentiation in the primitive stages of hematopoiesis. Overexpression of HMGB3 has been found in metastatic breast cancers [40]. In this study, HMGB3 was significantly enriched in GO terms associated with negative regulation of cell differentiation.…”
Section: Discussionsupporting
confidence: 52%
“…Recent study of Nemeth et al [39] showed that HMGB3 played a key role in regulating the balance between proliferation and differentiation in the primitive stages of hematopoiesis. Overexpression of HMGB3 has been found in metastatic breast cancers [40]. In this study, HMGB3 was significantly enriched in GO terms associated with negative regulation of cell differentiation.…”
Section: Discussionsupporting
confidence: 52%
“…Concordant with our data, Want et al recently implicated miR-320 in chemo-sensitivity by targeting FOXM1 in vitro , a critical gene which plays a principle role in colon, lung, and breast cancer tumor initiation and progression [2628]. Similarly, other investigators have also shown that FOXQ1 played a key role in nasopharyngeal carcinoma, targeted by miR-506 and miR-124 [29, 30]; likewise, HMGB3 in breast cancer is targeted by miR-205 [31]; and MKI67 in hepatocellular carcinoma, targeted by miR-519d [32]. …”
Section: Discussionmentioning
confidence: 99%
“…HMGB3 protein is highly expressed in the embryo and hardly detectable in adult tissues (Vaccari et al, 1998). HMGB3 expression is regulated by several miRNAs, including miR-206, miR-205, miR-10A, and miR-21 (Elgamal et al, 2013; Maciotta et al, 2012; Zhu et al, 2013c). HMGB3 −/− mice are viable and HMGB3 is required for eye and brain development (Terada et al, 2006).…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%
“…The formation of HMGB3-NPU98 fusion protein is a new oncogene identified in leukemia and significantly promotes malignant transformation in recipient mice (Petit et al, 2010). HMGB3 overexpression is associated with progression and poor prognosis of solid tumors such as breast, gastric, and non-small cell lung cancers (Elgamal et al, 2013; Gong et al, 2013; Song et al, 2013). However, the effect of HMGB3 in tumor therapy and the extracellular role of HMGB3 remain unknown.…”
Section: Introduction and Historical Backgroundmentioning
confidence: 99%